2004
DOI: 10.1029/2004gl021666
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Antarctic circumpolar transport and the Southern Annular Mode associated with the Madden‐Julian Oscillation

Abstract: The variability of oceanic Antarctic circumpolar transport and the atmospheric Southern Annular Mode (SAM) on intraseasonal (30–70‐day) timescales is shown to be related to the tropical atmospheric Madden‐Julian Oscillation (MJO) during southern winter. Approximately 7 days after anomalous MJO convection in the equatorial Indian Ocean peaks, an atmospheric extratropical response is set up with anomalous surface westerlies around almost the entire latitude circle at 60°S. This pattern projects strongly onto the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 21 publications
7
47
1
Order By: Relevance
“…The atmospheric MJO has a global structure (Hsu 1996) that can be well simulated in an atmospheric model if the MJO tropical heating pattern is correct (Matthews et al 2004). This will initiate a response in the extratropical oceans, such as that observed around the Antarctic coast from bottom pressure recorders (Matthews and Meredith 2004). The Argo float network is near-global.…”
Section: Discussionmentioning
confidence: 96%
“…The atmospheric MJO has a global structure (Hsu 1996) that can be well simulated in an atmospheric model if the MJO tropical heating pattern is correct (Matthews et al 2004). This will initiate a response in the extratropical oceans, such as that observed around the Antarctic coast from bottom pressure recorders (Matthews and Meredith 2004). The Argo float network is near-global.…”
Section: Discussionmentioning
confidence: 96%
“…Diverse studies have been developed that relate the interaction between variations within the synoptic scale and the MJO. Matthews and Kiladis (1999) studied the interaction between high-frequency transient disturbances and convection with the MJO. They found evidence that the propagation of high-frequency waves in the Indian Ocean could be of relevance for the onset of convective anomalies on an intraseasonal scale.…”
Section: Introductionmentioning
confidence: 99%
“…They found evidence that the propagation of high-frequency waves in the Indian Ocean could be of relevance for the onset of convective anomalies on an intraseasonal scale. For tropical-extratropical interactions, Matthews and Meredith (2004) and Zhou and Miller (2005) found that the variability of the atmospheric southern annular pattern on an intraseasonal scale shows a relation with the atmospheric variability related to the MJO during the southern winter.…”
Section: Introductionmentioning
confidence: 99%
“…Interdependence of the indices has been proposed by Carvalho et al (2005) who found that 25% of the AAO variance was linearly related to the state of ENSO. Given the similar time scales of the AAO and MJO (30-60 days), Matthews and Meredith (2004) suggested that seven days after convection in the equatorial Indian Ocean the AAO reaches a maximum. Conversely, Pohl et al (2010) argued that at intraseasonal time scales both the AAO and ENSO and also the AAO and MJO have insignificant correlations.…”
mentioning
confidence: 99%